«Die Gegenwart ist nichts als eine Hypothese». Formen und Funktionen von Experimentalität in Robert Musils «Der Mann ohne Eigenschaften» (Studia theodisca, 2015)
Based on the notion of experiments as “Experimentalsysteme” (Rheinberger) explicated by recent history of science studies the following paper examines how experiments are conducted in and are relevant to Robert Musil’s modern novel Der Mann ohne Eigenschaften on a thematic, textual, epistemological and poetological level. Focus areas are representations of different experimental constellations, i.e. scientific, poetic and thought experiments, the relation of experimental literary operations and scientific experimentation as well as Musil’s understanding of essayism as an experimental configuration between science and aesthetics.